Anode active material, method for producing anode active material, anode, and sodium ion battery

JP7640985B2Active Publication Date: 2025-03-06TOKYO UNIVERSITY OF SCIENCE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020176224
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-01
Filing Date
2020-10-20
Publication Date
2025-03-06
Estimated Expiration
2040-10-20

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、放電容量が高いナトリウムイオン電池が得られる負極活物質及びその製造方法、負極活物質を含む負極、並びに、負極を備えたナトリウムイオン電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640985000002
    Figure 0007640985000002
  • Figure 0007640985000001
    Figure 0007640985000001
Patent Text Reader

Abstract

To provide a negative electrode active material capable of obtaining a sodium ion battery having a high discharge capacity, a manufacturing method thereof, a negative electrode containing the negative electrode active material, and a sodium ion battery provided with the negative electrode.SOLUTION: There are provided negative electrode active material that includes a carbon material that has pores on the surface, in which the volume ratio of the pores is 28% to 60% with respect to the total volume of the carbon material, and the interlayer distance of the carbon material is 0.37 nm to 0.41 nm, and is used in a sodium ion battery, a manufacturing method of the negative electrode active material, a negative electrode 16, and a sodium ion battery 10.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode active material, a method for producing a negative electrode active material, a negative electrode, and a sodium ion battery. [Background technology]

[0002] Currently, non-aqueous electrolyte secondary batteries that use a non-aqueous electrolyte and are charged and discharged by transferring, for example, lithium ions between a positive electrode and a negative electrode are widely used as high energy density secondary batteries.

[0003] In such non-aqueous electrolyte secondary batteries, lithium transition metal composite oxides having a layered structure, such as lithium nickel oxide (LiNiO2) and lithium cobalt oxide (LiCoO2), are generally used as the positive electrode, and carbon materials capable of absorbing and releasing lithium, lithium metal, lithium alloys, etc. are used as the negative electrode.

[0004] As a secondary battery that can be charged and discharged, lithium-ion secondary batteries that can achieve high energy density at high voltages have been mainly used so far, but lithium resources are relatively limited and expensive. In addition, lithium resources are concentrated in South America, and Japan relies on imports for all of its resources. Therefore, in order to reduce costs and ensure a stable supply, sodium-ion secondary batteries are currently being developed as an alternative to lithium-ion secondary batteries.

[0005] For example, Patent Document 1 discloses a negative electrode active material for sodium ion secondary batteries, which comprises a porous carbon material having a plurality of open pores that communicate with the surface, a plurality of closed pores that do not communicate with the surface, and a solid portion made of a carbon material, in which the distance between carbon (002) planes in at least a part of the solid portion is 0.36 nm or more and 0.41 nm or less, and the volume ratio of the plurality of closed pores to the sum of the volumes of the plurality of open pores, the plurality of closed pores, and the solid portion is 30% or more and 90% or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2014 / 188722 Summary of the Invention [Problem to be solved by the invention]

[0007] There is a demand for even higher capacity sodium ion batteries.

[0008] In view of the above circumstances, an object of the present invention is to provide a negative electrode active material that enables a sodium ion battery with a high discharge capacity to be obtained, a method for producing the same, a negative electrode that includes the negative electrode active material, and a sodium ion battery that includes the negative electrode. [Means for solving the problem]

[0009] <1> A negative electrode active material for use in a sodium ion battery, comprising a carbon material having pores on its surface, the volume ratio of the pores being 28% to 60% of the total volume of the carbon material, and the interlayer distance of the carbon material being 0.37 nm to 0.41 nm. <2> The carbon material has an internal pore diameter of 1.0 nm to 1.6 nm as measured by small angle X-ray scattering. <1> The negative electrode active material according to claim 1. <3> Carbon materials have a helium true density of 1.7 g / cm 3 ~2.2g / cm 3 is <1> or <2> The negative electrode active material according to claim 1. <4> The carbon material has a true density of 1.10 g / cm 3 ~1.50g / cm 3 is <1> ~ <3> 13. The negative electrode active material according to claim 12, <5> The carbon material has a specific surface area of ​​400 m2 as measured by the BET method. 2 / g~800m 2 / g <1> ~ <4> 13. The negative electrode active material according to claim 12, <6> The carbon material has a surface pore volume of 0.1 cm as measured by the BET method. 3 / g~0.5cm 3 / g <1> ~ <5> 13. The negative electrode active material according to claim 12, <7> The carbon material has a surface pore diameter of 1.6 nm to 1.9 nm as measured by the BET method. <1> ~ <6> 13. The negative electrode active material according to claim 12, <8> <1> ~ <7> 13. A negative electrode comprising the negative electrode active material according to claim 12. <9> <8> A sodium ion battery comprising the negative electrode according to claim 1. <10> <1> ~ <7> The method for producing the negative electrode active material according to any one of the above items 1 to 5 includes a mixing step of mixing an organic acid magnesium with a sugar, and a calcination step of calcining the mixture at 1350°C to 1700°C to obtain a carbon material. <11> Between the mixing step and the firing step, the method further includes a heat treatment step of performing heat treatment at 500°C to 800°C, a washing step of washing the heat-treated product obtained by the heat treatment with an acid, and a drying step of drying the precursor obtained by washing. <10> 2. A method for producing the negative electrode active material according to claim 1 . <12> The mixing step includes a step of mixing an organic acid magnesium salt, sugar, and water to obtain an aqueous solution, and a step of freeze-drying the aqueous solution. <10> or <11> 2. A method for producing the negative electrode active material according to claim 1 . <13> The mixing ratio (molar ratio) of the organic acid magnesium to the sugar is 1:3 to 3:1. <10> ~ <12> 13. A method for producing a negative electrode active material according to claim 12. Effect of the Invention

[0010] According to the present invention, it is possible to provide a negative electrode active material that enables a sodium ion battery with high discharge capacity to be obtained, a method for producing the same, a negative electrode that includes the negative electrode active material, and a sodium ion battery that includes the negative electrode. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing an example of a sodium ion battery 10 according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The contents of the present invention will be described in detail below. The following description of the constituent elements may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, the word "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit. In this embodiment, a combination of two or more preferred aspects is a more preferred aspect.

[0013] <Negative electrode active material> The negative electrode active material according to this embodiment includes a carbon material having pores on the surface, the volume ratio of the pores is 28% to 60% with respect to the total volume of the carbon material, and the interlayer distance of the carbon material is 0.37 nm to 0.41 nm. The negative electrode active material according to this embodiment is used in a sodium ion battery. That is, the negative electrode active material according to this embodiment is a negative electrode active material for a sodium ion battery.

[0014] The negative electrode active material according to the present embodiment has a volume ratio of the open pores and an interlayer distance within the above ranges, so that a sodium ion battery having a high discharge capacity can be obtained. Although the reason why a sodium ion battery having a high discharge capacity can be obtained is not clear, it is thought to be as follows.

[0015] The negative electrode active material according to this embodiment contains a carbon material having openings on its surface, and the volume ratio of the openings is 28% to 60% of the total volume of the carbon material. In addition, the interlayer distance of the carbon material is 0.37 nm to 0.41 nm, which is believed to enable sodium ions to penetrate between the carbon atoms of the carbon material.

[0016] The negative electrode active material will be described in detail below.

[0017] (Carbon materials) The negative electrode active material according to the present embodiment includes a carbon material having open pores on the surface. Open pores refer to holes that have openings on the surface of the carbon material. On the other hand, closed pores refer to holes that do not have openings on the surface of the carbon material and are formed inside the carbon material. The carbon material preferably has both open pores and closed pores. The negative electrode active material preferably includes a carbon material that is composed of open pores, closed pores, and carbon portions.

[0018] The negative electrode active material may contain various additives in addition to the carbon material having pores on the surface. The carbon material having pores on the surface can be produced, for example, by the production method described below using an organic acid magnesium and sugar.

[0019] (Opening volume ratio) In the negative electrode active material according to this embodiment, the volume ratio of the open pores relative to the total volume of the carbon material is 28% to 60%, preferably 30% to 55%, more preferably 30% to 50%, and even more preferably 30% to 45%.

[0020] If the volume ratio of the open pores is 28% or more, a sodium ion battery with high discharge capacity can be obtained. From the viewpoint of manufacturability, the volume ratio of the open pores is 60% or less.

[0021] In this embodiment, the volume ratio of the open holes is calculated by the following formula: The volume ratio of the open holes calculated by the following formula is referred to as "volume ratio R1." R1 = (1-d B / d He ) x 100 In the formula, d B is the true density of the carbon material in butanol (g / cm 3 ), d He is the true helium density of the carbon material (g / cm 3 ) The butanol true density and helium true density of the carbon material will be described later.

[0022] The volume ratio of the open holes can also be calculated by the following formula: The volume ratio of the open holes calculated by the following formula is referred to as "volume ratio R2". R2=V OP / (V OP +1 / d He ) x 100 In the formula, V OP is the volume of the opening (cm 3 / g), d He is the true helium density of the carbon material (g / cm 3 ) means "V OP +1 / d He " is the total volume of the carbon material (cm 3 / g).

[0023] The pore volume is a value measured by a specific surface area / pore size distribution measuring device using nitrogen as an adsorption gas. A specific measuring method will be described in the examples. The true helium density of the carbon material will be described later.

[0024] (Butanol true density) In the negative electrode active material according to this embodiment, the carbon material has a butanol true density of 1.10 g / cm 3 ~1.50g / cm 3 and more preferably 1.10 g / cm 3 ~1.40g / cm 3 and more preferably 1.10 g / cm 3 ~1.30g / cm 3 It is.

[0025] The butanol true density of the carbon material is a value measured by a pycnometer method using butanol in accordance with the test method described in JIS R7212: 1995. The measurement is performed using a pycnometer, such as a Gay-Lussac type pycnometer manufactured by Shibata Scientific Co., Ltd.

[0026] (Helium true density) In the negative electrode active material according to this embodiment, the carbon material has a helium true density of 1.7 g / cm 3 ~2.2g / cm 3 and more preferably 1.8 g / cm 3 ~2.2g / cm 3and more preferably 1.9 g / cm 3 ~2.1g / cm 3 It is.

[0027] The helium true density of the carbon material is a value measured by a true density measuring device using helium. A specific measuring method will be described in the Examples.

[0028] In this specification, the densities measured using butanol and helium are both referred to as "true density." However, the carbon material constituting the negative electrode active material according to this embodiment has a very complicated structure and has pores inside, so strictly speaking, they can also be called "apparent density."

[0029] In the negative electrode active material according to this embodiment, the carbon material preferably has a ratio of the true density of helium to the true density of butanol of 1.13 to 2.25, more preferably 1.3 to 2.0, and further preferably 1.5 to 1.8.

[0030] (layer distance) In the negative electrode active material according to this embodiment, the interlayer distance of the carbon material is 0.37 nm to 0.41 nm, preferably 0.375 nm to 0.395 nm, and more preferably 0.38 nm to 0.39 nm.

[0031] If the interlayer distance of the carbon material is 0.37 nm or more, a sodium ion battery with high discharge capacity can be obtained. If the interlayer distance of the carbon material exceeds 0.41 nm, the surface area becomes large and the initial efficiency decreases. Therefore, the interlayer distance of the carbon material is 0.41 nm or less.

[0032] The interlayer distance of the carbon material is a value measured by a powder X-ray diffractometer. A specific measurement method will be described in the Examples.

[0033] (specific surface area) In the negative electrode active material according to the present embodiment, the carbon material has a specific surface area of ​​400 m2 as measured by the BET method in order to increase the discharge capacity. 2 / g~800m2 / g, more preferably 500m 2 / g~750m 2 / g.

[0034] The specific surface area of ​​the carbon material is a value measured by a specific surface area measuring device according to the BET method. A specific measuring method will be described in the Examples.

[0035] (Surface pore volume) In the negative electrode active material according to this embodiment, the carbon material has a surface pore volume of 0.1 cm as measured by the BET method in order to increase the discharge capacity. 3 / g~0.5cm 3 / g, and more preferably 0.2 cm 3 / g~0.4cm 3 / g.

[0036] The surface pore volume of the carbon material is a value measured by a pore distribution measuring device according to the BET method. A specific measuring method will be described in the Examples.

[0037] (Surface pore diameter) In the negative electrode active material according to this embodiment, from the viewpoint of increasing the discharge capacity, the carbon material preferably has a surface pore diameter measured by the BET method of 1.6 nm to 1.9 nm, more preferably 1.65 nm to 1.85 nm.

[0038] The surface pore diameter of the carbon material is a value measured by a pore size distribution measuring device according to the BET method. A specific measuring method will be described in the Examples.

[0039] (internal pore diameter) In the negative electrode active material according to this embodiment, from the viewpoint of increasing the discharge capacity, the carbon material preferably has an internal pore diameter measured by small angle X-ray scattering of 1.1 nm to 1.4 nm, more preferably 1.15 nm to 1.35 nm.

[0040] The internal pore diameter of the carbon material is a value measured by a powder X-ray diffractometer using a small angle X-ray scattering method. A specific measurement method will be described in the Examples.

[0041] <Method of manufacturing negative electrode active material> The method for producing the negative electrode active material according to this embodiment preferably includes a mixing step of mixing an organic acid magnesium with a sugar, and a calcination step of obtaining a carbon material by calcining the mixture at 1350° C. to 1700° C. That is, the negative electrode active material according to this embodiment is preferably a negative electrode active material produced by a production method including a mixing step of mixing an organic acid magnesium with a sugar, and a calcination step of calcining the mixture at 1350° C. to 1700° C. to obtain a carbon material.

[0042] Currently, there are limited methods for analyzing the specific structure of the carbon material produced by the manufacturing method including the mixing step and the baking step, and it is very difficult to distinguish it from carbon materials produced by other manufacturing methods. When the inventors analyzed the carbon material produced by such a manufacturing method, the carbon material had open pores on the surface, the volume ratio of the open pores was 28% to 60% of the total volume of the carbon material, and the interlayer distance of the carbon material was 0.37 nm to 0.41 nm. It was found that a sodium ion battery with a very high discharge capacity can be obtained by using the negative electrode active material produced by the manufacturing method including the mixing step and the baking step.

[0043] (Mixing process) The method for producing the negative electrode active material according to this embodiment includes a step of mixing an organic acid magnesium and a sugar.

[0044] The organic acid magnesium is a salt of magnesium and an organic acid, and examples thereof include magnesium gluconate, magnesium orotate, magnesium glycinate, magnesium glutamate, magnesium acetate, magnesium citrate, magnesium malate, magnesium benzoate, and magnesium stearate. Among these, from the viewpoint of solubility in water, the organic acid magnesium is preferably magnesium gluconate.

[0045] The sugar may be any of monosaccharides, disaccharides, oligosaccharides, and polysaccharides. The sugar is preferably a monosaccharide, specifically, glucose, galactose, and fructose. Among them, the sugar is preferably glucose from the viewpoint of solubility in water.

[0046] The mixing ratio (molar ratio) of the organic acid magnesium to the sugar is not particularly limited, but is preferably 1:3 to 3:1, more preferably 1:2 to 2:1, and further preferably 1:1.5 to 1.5:1.

[0047] The method of mixing the magnesium organic acid salt and the sugar is not particularly limited, but from the viewpoint of more uniform mixing of the magnesium organic acid salt and the sugar, it is preferable to mix the magnesium organic acid salt, the sugar, and water to obtain an aqueous solution. The concentration of the aqueous solution is not particularly limited, but from the viewpoint of more uniform mixing of the magnesium organic acid salt and the sugar, it is preferable that the concentration is 0.5 mol / L to 2.0 mol / L.

[0048] It is preferable that the aqueous solution containing the organic acid magnesium and the sugar is frozen and then sublimated under reduced pressure, that is, freeze-dried. The freeze-drying is carried out, for example, by using a freeze-drying apparatus (product name: "FDU-1100 type") manufactured by Tokyo Rikakikai Co., Ltd. for 10 minutes. 3 Pa~10 4 The pressure is 10 Pa.

[0049] After freeze-drying, the freeze-dried product obtained by freeze-drying is preferably pulverized. The pulverization method is not particularly limited, and any known pulverization method can be used.

[0050] That is, in the method for producing the negative electrode active material according to the present embodiment, the mixing step preferably includes a step of mixing the magnesium organic acid, sugar, and water to obtain an aqueous solution, and a step of freeze-drying the aqueous solution. In other words, the method for producing the negative electrode active material according to the present embodiment preferably includes a step of mixing the magnesium organic acid, sugar, and water to obtain an aqueous solution, a step of freeze-drying the aqueous solution, and a step of baking at 1350°C to 1700°C to obtain a carbon material. In addition, the negative electrode active material according to the present embodiment is more preferably a negative electrode active material produced by a production method including a step of mixing the magnesium organic acid, sugar, and water to obtain an aqueous solution, a step of freeze-drying the aqueous solution, and a step of baking at 1350°C to 1700°C to obtain a carbon material.

[0051] By using the negative electrode active material produced by the above-mentioned production method, a sodium ion battery with extremely high discharge capacity can be obtained.

[0052] (Firing process) The method for producing the negative electrode active material according to this embodiment includes a step of firing the mixture at 1350° C. to 1700° C. to obtain a carbon material.

[0053] This step is preferably carried out under an inert gas atmosphere. Examples of the inert gas include nitrogen gas and argon gas. The flow rate of the inert gas is preferably 50 mL / min to 300 mL / min.

[0054] The firing method is not particularly limited, and is performed, for example, using a tubular furnace. The firing temperature is preferably 1350°C to 1700°C, and more preferably 1400°C to 1600°C. It is believed that firing the mixture at 1350°C to 1700°C makes the structure of the carbon material more suitable for storing sodium ions. The rate of temperature increase up to the final temperature is preferably 5°C / min to 20°C / min. The firing time after the final temperature is reached is preferably 30 minutes to 2 hours.

[0055] After the calcination, it is preferable to cool the product to room temperature and pulverize the product obtained by the calcination. The pulverized product may be used as it is as the negative electrode active material, or the product mixed with an additive may be used as the negative electrode active material. The pulverization method is not particularly limited, and a known pulverization method may be used.

[0056] (Other processes) The method for producing the negative electrode active material according to this embodiment may include steps other than the mixing step and the firing step.

[0057] Specifically, it is preferable to further include, between the mixing step and the firing step, a heat treatment step of performing heat treatment at 500°C to 800°C, a washing step of washing the heat-treated product obtained by the heat treatment with an acid, and a drying step of drying the precursor obtained by washing.

[0058] The heat treatment step is preferably carried out under an inert gas atmosphere. Examples of the inert gas include nitrogen gas and argon gas. The flow rate of the inert gas is preferably 50 mL / min to 300 mL / min.

[0059] The heat treatment method is not particularly limited, and is carried out, for example, using a tubular furnace. The heat treatment temperature is preferably 500°C to 800°C, more preferably 500°C to 700°C, and further preferably 550°C to 650°C. It is believed that by heat treating the mixture in advance and then firing it, the structure of the carbon material becomes more suitable for storing sodium ions. The rate of temperature increase up to the final temperature is preferably 5°C / min to 20°C / min. The heat treatment time after the final temperature is reached is preferably 30 minutes to 2 hours.

[0060] After the heat treatment, it is preferable to allow the product to cool to room temperature and then pulverize the product obtained by the heat treatment. The pulverization method is not particularly limited, and any known pulverization method can be used.

[0061] In the washing step, the type of acid is not particularly limited, but from the viewpoint of ease of handling, hydrochloric acid is preferable. From the viewpoint of washing efficiency, the concentration of hydrochloric acid is preferably 0.5 mol / L to 2 mol / L.

[0062] The cleaning method is not particularly limited, and any known method can be used. From the viewpoint of cleaning efficiency, it is preferable to perform cleaning while applying ultrasonic vibration to the acid solution serving as the cleaning liquid.

[0063] The cleaning time is not particularly limited and is, for example, 30 minutes to 2 hours.

[0064] After washing with acid, the acid-washed mixture is preferably washed with ion-exchanged water until the electrical conductivity of the water discharged by washing is 0.2 mS / m or less.

[0065] After washing with ion-exchanged water, it is preferable to dry the precursor obtained by washing. Drying is performed under reduced pressure, for example, at a pressure of 1000 Pa to 20000 Pa. The drying temperature is, for example, 80°C to 120°C.

[0066] That is, the method for producing the negative electrode active material according to the present embodiment further preferably includes a step of mixing an organic acid magnesium, sugar, and water to obtain an aqueous solution, a step of freeze-drying the aqueous solution, a heat treatment step of performing heat treatment at 500°C to 800°C, a washing step of washing the heat-treated product obtained by the heat treatment with an acid, a drying step of drying the precursor obtained by washing, and a firing step of firing the precursor at 1350°C to 1700°C to obtain a carbon material. Moreover, the negative electrode active material according to the present embodiment is further preferably a negative electrode active material produced by a production method including a step of mixing an organic acid magnesium, sugar, and water to obtain an aqueous solution, a step of freeze-drying the aqueous solution, a heat treatment step of performing heat treatment at 500°C to 800°C, a washing step of washing the heat-treated product obtained by the heat treatment with an acid, a drying step of drying the precursor obtained by washing, and a firing step of firing the precursor at 1350°C to 1700°C to obtain a carbon material.

[0067] By using the negative electrode active material produced by the above-mentioned production method, a sodium ion battery with extremely high discharge capacity can be obtained.

[0068] <Negative electrode> The negative electrode according to the present embodiment includes the negative electrode active material according to the present embodiment. Examples of the negative electrode include one made of the negative electrode active material, and one having a current collector and a negative electrode active material layer formed on the surface of the current collector, the negative electrode active material layer including the negative electrode active material and an additive. Examples of the additive include a conductive agent and a binder.

[0069] Examples of the conductive agent include carbon such as carbon black, graphite, carbon nanotubes (CNT), and vapor grown carbon fiber (VGCF).

[0070] Examples of carbon black include acetylene black, oil furnace black, and ketjen black. Among them, from the viewpoint of electrical conductivity, at least one selected from the group consisting of acetylene black and ketjen black is preferable, and acetylene black or ketjen black is more preferable.

[0071] The conductive agent may be used alone or in combination of two or more. The content of the conductive agent in the negative electrode active material layer is not particularly limited, but is preferably 1% by mass to 30% by mass, more preferably 2% by mass to 20% by mass, and even more preferably 3% by mass to 10% by mass, based on the total mass of the negative electrode active material layer. When it is within the above range, a negative electrode with higher output can be obtained, and the durability of the negative electrode is excellent.

[0072] -Binding agent- The binder is not particularly limited, and any known binder may be used, for example, a polymer compound. Specific examples of the polymer compound include fluororesin, polyolefin resin, rubber polymer, polyamide, polyimide, polyamideimide, glutamic acid, starch, cellulose-based compound, polyacrylic acid, sodium polyacrylate, and polyacrylonitrile.

[0073] Examples of fluororesins include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene fluororubber (VDF-HFP fluororubber), and vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene fluororubber (VDF-HFP-TFE fluororubber).

[0074] Examples of polyolefin resins include polyethylene, syndiotactic-1,2-polybutadiene, ethylene-vinyl acetate copolymer, and propylene-α-olefin (having 2 to 12 carbon atoms) copolymer.

[0075] Examples of rubber-like polymers include styrene-butadiene rubber, isoprene rubber, butadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymers and hydrogenated products thereof, styrene-ethylene-butadiene-styrene copolymers, and styrene-isoprene-styrene block copolymers and hydrogenated products thereof.

[0076] Cellulosic compounds include cellulose, methyl cellulose, carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, carboxymethyl hydroxyethyl cellulose, and nitrocellulose.

[0077] Among these, the binder is preferably sodium polyacrylate, from the viewpoints that water can be used as a dispersion medium and that it has excellent binding power.

[0078] The binder may be used alone or in combination of two or more. The content of the binder in the negative electrode active material layer is not particularly limited, but is preferably 1% by mass to 30% by mass, more preferably 2% by mass to 20% by mass, and even more preferably 5% by mass to 15% by mass, based on the total mass of the negative electrode active material layer. When the content is within the above range, the negative electrode has excellent moldability and durability.

[0079] The method for producing a negative electrode containing a negative electrode active material, a conductive agent, and a binder is not particularly limited, and may be, for example, a method in which the negative electrode active material, the conductive agent, and the binder are mixed together and pressure-molded, or a method in which a slurry described below is prepared and then coated on a current collector.

[0080] Examples of the current collector include foils, meshes, expanded grids (expanded metals), and punched metals made of conductive materials such as nickel, aluminum, and stainless steel (SUS). The mesh openings, wire diameter, and number of meshes are not particularly limited. The current collector is preferably an aluminum current collector.

[0081] The method of forming the negative electrode on the current collector is not particularly limited, but includes a method of preparing a slurry by mixing a negative electrode active material, an additive, and a solvent, and applying the slurry onto the current collector. Examples of the solvent include amines such as N,N-dimethylaminopropylamine and diethyltriamine, ethers such as ethylene oxide and tetrahydrofuran, ketones such as methyl ethyl ketone, esters such as methyl acetate, aprotic polar solvents such as dimethylacetamide and N-methyl-2-pyrrolidone, and water.

[0082] The negative electrode is produced, for example, by applying the prepared slurry onto a current collector and drying it. Examples of methods for applying the slurry onto a current collector include slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying.

[0083] The shape and size of the negative electrode according to this embodiment are not particularly limited, and may be adapted to the shape and size of the battery to be used.

[0084] The negative electrode according to this embodiment may contain only one type of negative electrode active material, or may contain two or more types. The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably 80% by mass to 95% by mass.

[0085] <Sodium ion battery> The sodium ion battery according to this embodiment is a sodium ion battery including the negative electrode according to this embodiment. The sodium ion battery according to this embodiment can be suitably used as a sodium ion secondary battery.

[0086] The sodium ion battery according to this embodiment preferably includes a positive electrode and an electrolyte in addition to the negative electrode, and more preferably includes a positive electrode, an electrolyte, and a separator in addition to the negative electrode.

[0087] The sodium ion battery according to this embodiment may include various known materials used in lithium ion batteries, such as a battery case, spacers, gaskets, and springs.

[0088] The method for producing the sodium ion battery according to the present embodiment is not particularly limited, and can be carried out according to a known method. The shape of the battery to be produced is not particularly limited, and examples thereof include various shapes such as a cylindrical shape, a square shape, and a coin shape.

[0089] (positive electrode) The sodium ion battery according to the present embodiment preferably includes a positive electrode. The positive electrode preferably includes a positive electrode active material. The positive electrode may also include a compound other than the positive electrode active material.

[0090] The other compounds are not particularly limited, and known additives used in the manufacture of a positive electrode of a battery can be used. Examples of the additives include a conductive agent, a binder, and a current collector. The conductive agent, the binder, and the current collector can be the same as those described above.

[0091] The shape and size of the positive electrode according to this embodiment are not particularly limited, and can be made to a desired shape and size according to the shape and size of the battery to be used.

[0092] The positive electrode active material is not particularly limited, and any known positive electrode active material for sodium ion batteries can be used. From the viewpoint of charge / discharge capacity and output characteristics, the positive electrode active material for sodium ion batteries is preferably a sodium-containing compound, and more preferably a sodium-transition metal complex oxide. Examples of sodium-transition metal complex oxides include NaMn2O4, NaNiO2, NaCoO2, NaFeO2, and NaNi 0.5 Mn 0.5 O2 and NaNi 0.5 Ti 0.5 O2 is one example.

[0093] (electrolyte) The sodium ion battery according to this embodiment preferably includes an electrolyte.

[0094] The electrolyte is not particularly limited as long as it contains a sodium salt as the main electrolyte. In the case of an aqueous electrolyte, examples of the sodium salt include NaClO4, NaPF6, NaNO3, NaOH, NaCl, Na2SO4, and Na2S.

[0095] In addition, in the case of a non-aqueous electrolyte, examples of the sodium salt include NaPF6, NaBF4, CF3SO3Na, NaAsF6, NaB(C6H5)4, CH3SO3Na, NaN(SO2CF3)2, NaN(SO2C2F5)2, NaC(SO2CF3)3, and NaN(SO3CF3)2). These sodium salts may be used alone or in combination of two or more. Among them, the sodium salt is preferably NaPF6.

[0096] The electrolyte preferably contains a sodium salt and a solvent, such as carbonates such as propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, isopropyl methyl carbonate, vinylene carbonate, fluoroethylene carbonate, 4-trifluoromethyl-1,3-dioxolan-2-one, and 1,2-di(methoxycarbonyloxy)ethane; Ethers such as 1,2-dimethoxyethane, 1,3-dimethoxypropane, pentafluoropropyl methyl ether, 2,2,3,3-tetrafluoropropyl difluoromethyl ether, tetrahydrofuran, and 2-methyltetrahydrofuran; Esters such as methyl formate, methyl acetate, and gamma-butyrolactone; Nitriles such as acetonitrile, butyronitrile, etc.; Amides such as N,N-dimethylformamide, N,N-dimethylacetamide; Carbamates such as 3-methyl-2-oxazolidone; Sulfur-containing compounds such as sulfolane, dimethyl sulfoxide, and 1,3-propane sultone; and compounds in which hydrogen atoms in the above compounds are substituted with fluorine atoms.

[0097] The solvent may be used alone or in combination of two or more kinds, but it is preferable to use a mixture of two or more kinds.

[0098] Among them, the solvent is preferably at least one solvent selected from the group consisting of propylene carbonate, ethylene carbonate, and diethyl carbonate, and more preferably a mixed solvent of at least two solvents selected from the group consisting of propylene carbonate, ethylene carbonate, and diethyl carbonate.

[0099] The concentration of the sodium salt in the electrolyte is not particularly limited, but is preferably 0.1 mol / L or more and 2 mol / L or less, and more preferably 0.5 mol / L or more and 1.5 mol / L or less.

[0100] (Separator) The sodium ion battery according to this embodiment preferably includes a separator.

[0101] The separator serves to physically isolate the positive electrode and the negative electrode and to prevent internal short circuits. The separator is made of a porous material, the pores of which are impregnated with an electrolyte, and has ion permeability (particularly, permeability to at least sodium ions) in order to ensure the battery reaction.

[0102] Examples of the separator include a resin porous membrane and a nonwoven fabric. The separator may be a single layer of a porous membrane or a nonwoven fabric, or a laminate of multiple layers. Examples of the laminate include a laminate having multiple porous membrane layers with different compositions, and a laminate having a porous membrane layer and a nonwoven fabric layer.

[0103] The material of the separator can be selected in consideration of conditions such as the temperature at which the battery is used and the composition of the electrolyte. Examples of resins contained in the fibers forming the porous membrane and nonwoven fabric include polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymer; polyphenylene sulfide resins such as polyphenylene sulfide and polyphenylene sulfide ketone; polyamide resins such as aromatic polyamide resins; and polyimide resins. These resins may be used alone or in combination of two or more. The fibers forming the nonwoven fabric may be inorganic fibers such as glass fibers.

[0104] The separator is preferably a separator containing at least one material selected from the group consisting of glass, polyolefin resin, polyamide resin, and polyphenylene sulfide resin, and among them, a filter made of glass fiber is preferable as the separator.

[0105] The separator may contain an inorganic filler. Examples of the inorganic filler include ceramics (e.g., silica, alumina, zeolite, and titania), talc, mica, and wollastonite. The inorganic filler is preferably in the form of particles or fibers.

[0106] The content of the inorganic filler in the separator is preferably 10% by mass to 90% by mass, and more preferably 20% by mass to 80% by mass.

[0107] The shape and size of the separator are not particularly limited and may be appropriately selected according to the desired shape of the battery.

[0108] Fig. 1 is a schematic diagram showing an example of the configuration of a sodium ion battery 10 according to this embodiment. However, the sodium ion battery according to this embodiment is not limited to this. The sodium ion battery 10 shown in Fig. 1 is a coin-type battery, and includes a battery case 12, a gasket 14, a negative electrode 16, a separator 18, a positive electrode 20, a spacer 22, a spring 24, and a battery case 26 on the positive electrode side. The separator 18 is impregnated with an electrolyte (not shown). EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention.

[0110] <Preparation of negative electrode active material> Example 1 -Mixing process (liquid phase mixing)- 6 mmol of magnesium (II) gluconate hydrate (Tokyo Chemical Industry Co., Ltd.), 6 mmol of D-glucose (Kanto Chemical Co., Ltd.), and 60 mL of water were added to a flask and stirred for 10 minutes to mix. In other words, liquid phase mixing was performed. Next, the mixture was freeze-dried for 24 hours under a pressure of 6 Pa using a freeze-drying device (product name "FDU-1100 type", Tokyo Rikakikai Co., Ltd.). The freeze-dried product was pulverized using an agate mortar.

[0111] -Heat treatment process- The pulverized material obtained in the mixing step was heat-treated in a tubular furnace under an argon gas atmosphere at 600°C for 1 hour. The gas flow rate was 200 mL / min, and the temperature increase rate to the final temperature (600°C) was 10°C / min. After the heat treatment, the material was allowed to cool to room temperature. The heat-treated material obtained was pulverized using an agate mortar.

[0112] -Cleaning process- The ground material obtained in the heat treatment process was washed with 1 mol / L hydrochloric acid while applying ultrasonic vibrations using an ultrasonic cleaning device (product name "ASU CLEANER ASU-3M", manufactured by AS ONE Corporation). The acid-washed material was washed with ion-exchanged water, and it was confirmed that the electrical conductivity of the water discharged by washing was 0.2 mS / m or less.

[0113] -Drying process- The precursor obtained in the washing step was dried at 110° C. under a pressure of 2000 Pa for 3 days.

[0114] - Firing process - The dried product obtained in the drying process was heat-treated in a tubular furnace under an argon gas atmosphere at 1500°C for 1 hour. The gas flow rate was 200mL / min, and the temperature increase rate to the final temperature (1500°C) was 10°C / min. After firing, the product was allowed to cool to room temperature. The fired product obtained was pulverized using an agate mortar to obtain a negative electrode active material.

[0115] (Example 2, Comparative Example 1, Reference Example 1, Reference Example 2, Reference Examples 5 to 7) A negative electrode active material was obtained in the same manner as in Example 1, except that in the mixing step, the mixing ratio of magnesium gluconate (II) hydrate and D-glucose was changed to the mixing ratio shown in Table 1.

[0116] (Reference example 3) A negative electrode active material was obtained in the same manner as in Example 1, except that in the mixing step, D-glucose was not used, and 10 mmol of magnesium gluconate (II) hydrate and 100 mL of water were added to a flask, stirred for 10 minutes, and mixed. Since magnesium gluconate (II) hydrate and D-glucose were not mixed, the mixing ratio in Table 1 is described as "1:0".

[0117] (Reference example 4) A negative electrode active material was obtained in the same manner as in Example 1, except that in the mixing step, magnesium gluconate (II) hydrate was not used, and 10 mmol of D-glucose and 100 mL of water were added to a flask, stirred for 10 minutes, and mixed. Since magnesium gluconate (II) hydrate and D-glucose were not mixed, the mixing ratio in Table 1 is described as "0:1".

[0118] (Reference example 8) A negative electrode active material was obtained in the same manner as in Example 1, except that the pulverized material obtained in the heat treatment step was not subjected to the washing step but was subjected to the firing step.

[0119] (Reference example 9) In Example 1, liquid phase mixing was performed in the mixing step, whereas in Reference Example 9, a negative electrode active material was obtained in the same manner as in Example 1, except that powder mixing was performed. -Mixing process (powder mixing)- 6 mmol of magnesium gluconate (II) hydrate (Tokyo Chemical Industry Co., Ltd.) and 6 mmol of D-glucose (Kanto Chemical Co., Ltd.) were placed in an ointment container. The ointment container was set in a planetary centrifugal mixer (product name "ARE-310", Thinky Corporation) and stirred. The mixture was removed from the ointment container and pulverized in an agate mortar.

[0120] (Reference example 10, reference example 11) A negative electrode active material was obtained in the same manner as in Example 9, except that in the mixing step, the mixing ratio of magnesium (II) gluconate hydrate and D-glucose was changed to the mixing ratio shown in Table 1.

[0121] (Reference example 12) A negative electrode active material was obtained in the same manner as in Example 1, except that the mixing step was not performed and 10 mmol of magnesium gluconate (II) hydrate was used in the heat treatment step. Since magnesium gluconate (II) hydrate and D-glucose were not mixed, the mixing ratio in Table 1 is described as "1:0".

[0122] (Reference example 13) A negative electrode active material was obtained in the same manner as in Example 1, except that the mixing step was not performed and 10 mmol of D-glucose was used in the heat treatment step. Since magnesium (II) gluconate hydrate and D-glucose were not mixed, the mixing ratio in Table 1 is described as "0:1."

[0123] The prepared negative electrode active material was measured for the pore volume ratio (R1, R2), interlayer distance, butanol true density, helium true density, true density ratio, specific surface area, surface pore volume, surface pore diameter, and internal pore diameter. The measurement methods are as follows. The true density ratio means the helium true density relative to the butanol true density. The measurement results are shown in Table 1. In Table 1, blank spaces indicate that no measurements were made.

[0124] [Opening volume ratio] -Opening volume ratio R1- The open pore volume ratio R1 was calculated using the following formula. R1 = (1-d B / d He ) x 100 In the formula, d B is the true density of the carbon material in butanol (g / cm 3 ), d He is the true helium density of the carbon material (g / cm 3 ) -Opening volume ratio R2- The volume ratio R2 of the open holes was calculated using the following formula. R2=V OP / (V OP +1 / d He ) x 100 In the formula, V OP is the volume of the opening (cm 3 / g), d He is the true helium density of the carbon material (g / cm 3 ) means "V OP +1 / d He " is the total volume of the carbon material (cm 3 / g). The volume of the open pores was measured by a specific surface area / pore size distribution measuring device (product name "Belsorp-miniII", manufactured by MicrotrackBell) using nitrogen as the adsorption gas. The measurement method is as follows. To remove water adsorbed in the pores of the sample, the sample was pretreated by vacuum drying at 300°C for 5 hours before the measurement. The measurement temperature was 77K, and nitrogen was used as the adsorption gas. The amount of adsorption was measured by repeating gas introduction and adsorption until the equilibrium pressure reached the target relative pressure on the adsorption side. The amount of desorption was measured by repeating pressure reduction and desorption until the equilibrium pressure reached the target relative pressure on the desorption side. Opening volume V OP is the amount of adsorbed gas V (cm) at a relative pressure of 0.99 in the obtained adsorption isotherm data. 3 / g -1 ) was converted to the volume of the adsorbate in the liquid state using the following formula: V OP =(V / 22414)×(M g / ρ g ) In the formula, M g is the molecular weight of the adsorbate, ρ g is the density of the adsorbate (g / cm 3 )

[0125] Layer Distance The interlayer distance was measured using a powder X-ray diffractometer (product name "SmartLab (registered trademark)" manufactured by Rigaku Corporation) according to the following method. The sample was packed in a glass sample holder, and a Cu tube was used as the X-ray source. Kβ rays were attenuated with a Ni filter. The tube voltage was set to 40 kV, the tube current to 45 mA, and a high-speed one-dimensional detector (product name "D / teX Ultra250", manufactured by Rigaku Corporation) was used as the detector. Measurements were performed with a Bragg-Brentano type optical system, with a measurement range of 10° to 80° and a step width of 0.02°. Peak fitting of the measured diffraction lines was performed using the curve fitting program fityk. Specifically, first, a straight line connecting two minimum points in the diffraction lines was used as the background. Next, the position of the diffraction line was examined by selecting only the 002 diffraction line and performing peak fitting. The function used was PseudoVoigt. The interlayer distance was calculated from the 002 peak position using the Bragg equation.

[0126] [Butanol true density] The measurement was performed in accordance with the test method described in JIS R7212:1995 using a Gay-Lussac type pycnometer manufactured by Shibata Scientific Co., Ltd.

[0127] [Helium true density] The true density of helium was measured using a true density measuring device (product name "BELPycno", manufactured by MicrotrackBell Co., Ltd.) The measurement method is as follows. The ambient temperature during the measurements was kept constant at 25° C. All pressures in these measurements were gauge pressures, which are absolute pressures minus ambient pressure. The measuring device includes a sample chamber and an expansion chamber, and the sample chamber is equipped with a pressure gauge for measuring the pressure inside the chamber. The sample chamber and the expansion chamber are connected by a connecting pipe equipped with a valve. A helium gas inlet pipe equipped with a valve is connected to the sample chamber, and a helium gas outlet pipe equipped with a valve is connected to the expansion chamber. First, the volume of the sample chamber V CELL (cm 3 ) and the volume of the expansion chamber V EXP (cm 3) was measured in advance using a standard sphere. A sample was placed in the sample chamber, and helium gas was purged three times through the helium gas inlet pipe of the sample chamber, the connecting pipe, and the helium gas outlet pipe of the expansion chamber, for pretreatment. Next, the valve between the sample chamber and the expansion chamber and the valve of the helium gas outlet pipe connected to the expansion chamber were closed. As a result, helium gas at the same pressure as the ambient pressure remained in the expansion chamber. Helium gas was introduced into the sample chamber through the helium inlet pipe until it reached 145 kPa, and then the valve of the helium gas inlet pipe was closed. The pressure P1 of the sample chamber in the equilibrium state (specifically, a state in which there was no pressure change of 60 Pa or more for 30 seconds) was measured. Next, the pressure P2 of the entire system including the sample chamber and the expansion chamber was measured when the valve between the sample chamber and the expansion chamber was opened and helium gas was transferred to the expansion chamber. Measurements were continued until the accuracy of the 10 measurement results was within 0.10%. Sample volume V SAMP (cm 3 ) was calculated based on the following formula. V SAMP =V CELL -V EXP / {(P1 / P2)-1} Helium true density d He (g / cm 3 ) was calculated based on the following formula. d He =V SAMP / W SAMP In the formula, W SAMP means the weight of the sample (g).

[0128] [True density ratio] Based on the measured true density of butanol and true density of helium, the true density of helium relative to the true density of butanol was calculated.

[0129] [Specific surface area] The specific surface area was measured using a specific surface area / pore distribution measuring device (product name "Belsorp-miniII", manufactured by MicrotrackBell Co., Ltd.) The measurement method is as follows. To remove water adsorbed in the pores of the sample, the sample was pretreated by vacuum drying at 300°C for 5 hours before measurement. The measurement temperature was 77K, and nitrogen gas was used as the adsorption gas. The amount of adsorption was measured by repeating gas introduction and adsorption until the equilibrium pressure reached the target relative pressure on the adsorption side. The amount of desorption was measured by repeating decompression and desorption until the equilibrium pressure reached the target relative pressure on the desorption side. The surface area is given by an approximation derived from the BET equation, V m =V α It was calculated by the one-point method using nitrogen adsorption at liquid nitrogen temperature using (1-p / p0). m is the amount of adsorption (cm) required to form a monolayer on the sample surface. 3 / g), V α is the measured amount of adsorption (cm 3 / g), p / p0 is the relative pressure. The specific surface area S is the amount of adsorption sufficient to form a monolayer (monolayer adsorption amount V m (cm 3 / g) and the area occupied by the adsorbed gas molecules in the solid state (molecular occupancy cross-sectional area (nm 2 The molecular cross section of nitrogen is 0.162 nm 2 Therefore, the specific surface area S (m 2 / g) was calculated. S=4.35V m

[0130] [Surface pore volume] The surface pore volume was measured using a specific surface area / pore distribution measuring device (product name "Belsorp-miniII", manufactured by MicrotrackBell Co., Ltd.) The measurement method is as follows. To remove water adsorbed in the pores of the sample, the sample was pretreated by vacuum drying at 300°C for 5 hours before measurement. The measurement temperature was 77K, and nitrogen gas was used as the adsorption gas. The amount of adsorption was measured by repeating gas introduction and adsorption until the equilibrium pressure reached the target relative pressure on the adsorption side. The amount of desorption was measured by repeating decompression and desorption until the equilibrium pressure reached the target relative pressure on the desorption side. The surface area is given by an approximation derived from the BET equation, V m =V αIt was calculated by the one-point method using nitrogen adsorption at liquid nitrogen temperature using (1-p / p0). m is the amount of adsorption (cm) required to form a monolayer on the sample surface. 3 / g), V α is the measured amount of adsorption (cm 3 / g), p / p0 is the relative pressure. The surface pore volume was calculated by liquid displacement of the adsorbed amount at a relative pressure of 0.99.

[0131] [Surface pore diameter] The surface pore diameter is the volume V of the above open pores. OP (cm 3 / g) and the specific surface area S(m 2 / g) based on the following formula: Surface pore diameter (nm) = (4 × V OP ) / S×10 3

[0132] [Internal pore diameter] The internal pore diameter was measured using a powder X-ray diffractometer (product name "SmartLab (registered trademark)", manufactured by Rigaku Corporation) according to the following method. The sample was packed into a borosilicate glass capillary, and a Cu tube was used as the X-ray source, with a tube voltage of 40 kV and a tube current of 45 mA. A scintillation counter (product name "SC-70", manufactured by Rigaku Corporation) was used as the detector, with an angle range of 0.06° to 9.98° and a scan speed of 0.99° min -1 The measurements were performed under the following conditions: The obtained spectrum was fitted using particle size / pore size analysis software (product name "NANO-Solver3.7", manufactured by Rigaku Corporation), and the pore diameter was calculated assuming that the pores were spherical.

[0133] <Preparation of working electrode> The prepared negative electrode active material, acetylene black (product name "Li-400", manufactured by Denka Co., Ltd.) as a conductive agent, and sodium polyacrylate (manufactured by Kishida Chemical Co., Ltd.) as a binder were weighed out to a weight ratio of 85:5:10, and mixed with water as a solvent to obtain a slurry. The obtained slurry was applied to a current collector (aluminum foil, manufactured by Hosen Co., Ltd., thickness 0.017 mm) using a doctor blade. The coated material was dried in a dryer at 80°C for 2 hours, and then vacuum dried at 150°C for 12 hours to obtain an electrode sheet. The electrode sheet was punched out into a circle with a diameter of 10 mm using an electrode punching machine to obtain a working electrode.

[0134] <Preparation of counter electrode> Sodium metal (Kanto Chemical Co., Ltd.) was punched out into a circle with a diameter of 10 mm using an electrode punching machine to serve as the counter electrode.

[0135] <Preparation of electrolyte> An electrolyte solution was prepared by dissolving 1 molar sodium hexafluorophosphate (Kishida Chemical Co., Ltd.) in a solution in which ethylene carbonate and diethyl carbonate were mixed in a volume ratio of 1:1.

[0136] <Preparation of sodium ion battery (half cell) for measurement> In this example, a working electrode was produced using the negative electrode active material, and sodium metal was used as a counter electrode to evaluate the negative electrode characteristics of a sodium ion battery as a half cell. The sodium ion battery for measurement was prepared in a glove box with an argon gas atmosphere. The prepared working electrode, separator (product name "GB-100R", circular glass fiber filter paper with a thickness of 380 μm and a diameter of 1.8 cm), and counter electrode were stacked in this order. This was placed in a SUS battery case, and the prepared electrolyte was injected. A polypropylene gasket (product name "CR2032", manufactured by Hosen Co., Ltd.), a spacer (material: SUS, diameter 16 mm x height 0.5 mm, manufactured by Hosen Co., Ltd.), and a leaf spring (material: SUS, inner diameter 10 mm, height 2.0 mm, thickness 0.25 mm, washer manufactured by Hosen Co., Ltd.) were used to seal the battery, and a sodium ion battery (half cell) for measurement was obtained. The amount of electrolyte injected was set to an amount (200 μl) that sufficiently filled the separator with electrolyte.

[0137] A charge / discharge test was carried out using the prepared sodium ion battery for measurement. The charge / discharge test method was as follows. The evaluation results are shown in Table 1.

[0138] [Charge / discharge test] The prepared sodium ion battery for measurement was left for 24 hours. Next, a charge / discharge test was performed using the prepared sodium ion battery for measurement under the conditions of a current density of 25 mA / g, a charge cut-off voltage of 0.002 V (after reaching the cut-off voltage, the cut-off voltage was held for 8 hours), a rest time after charge of 5 minutes, a discharge cut-off voltage of 2 V, and a rest time after discharge of 5 minutes. A charge / discharge tester (product name "TOSCAT-3100", manufactured by Toyo Systems Co., Ltd.) was used for the charge / discharge test. The coulombic efficiency was calculated based on the charge capacity per unit weight and the discharge capacity per unit weight obtained by the measurement. Coulombic efficiency (%) = (discharge capacity per unit weight / charge capacity per unit weight) x 100

[0139] [Table 1]

[0140] As shown in Table 1, it was found that the sodium ion batteries using the negative electrode active materials of Example 1 and Example 2 had very high discharge capacities.

[0141] On the other hand, in Comparative Example 1, since the volume ratio R1 of the open pores was less than 28%, it was found that the discharge capacity was low. [Explanation of symbols]

[0142] 10: sodium ion battery, 12: battery case (negative electrode side), 14: gasket, 16: negative electrode, 18: separator, 20: positive electrode, 22: spacer, 24: leaf spring, 26: battery case (positive electrode side)

Claims

1. A carbon material having openings on a surface thereof, The volume ratio R1 of the open holes represented by the following formula is 28% to 60%, and the interlayer distance of the carbon material is 0.37 nm to 0.41 nm; The carbon material has a specific surface area of ​​400 m 2 / g to 800 m 2 / g as measured by a BET method. A negative electrode active material used in sodium ion batteries. R1=(1-dB / dHe)×100 In the formula, d B represents the true density of the carbon material in butanol (g / cm 3 ), and d He represents the true density of the carbon material in helium (g / cm 3 ).

2. 2. The negative electrode active material according to claim 1, wherein the carbon material has an internal pore diameter of 1.0 nm to 1.6 nm as measured by a small angle X-ray scattering method.

3. The carbon material has a helium true density of 1.7 g / cm 3 ~2.2g / cm 3 The negative electrode active material according to claim 1 or 2,

4. The carbon material has a butanol true density of 1.10 g / cm 3 ~1.50g / cm 3 The negative electrode active material according to any one of claims 1 to 3,

5. The carbon material has a surface pore volume of 0.1 cm as measured by the BET method. 3 / g to 0.5 cm 3 The negative electrode active material according to any one of claims 1 to 4, wherein the molecular weight of the negative electrode active material is 1 / g.

6. 6. The negative electrode active material according to claim 1, wherein the carbon material has a surface pore diameter measured by a BET method of 1.6 nm to 1.9 nm.

7. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 6.

8. A sodium ion battery comprising the negative electrode according to claim 7.

9. A method for producing the negative electrode active material according to any one of claims 1 to 6, A mixing step of mixing an organic acid magnesium salt and sugar; and a calcination step of calcining the mixture obtained in the mixing step at 1350° C. to 1700° C. to obtain a carbon material.

10. Between the mixing step and the firing step, a heat treatment step of heat treating the mixture obtained in the mixing step at 500°C to 800°C; a washing step of washing the heat-treated product obtained by the heat treatment with an acid; The method for producing a negative electrode active material according to claim 9 , further comprising a drying step of drying the precursor obtained by washing.

11. The mixing step comprises: mixing the organic acid magnesium salt, the sugar, and water to obtain an aqueous solution; freeze-drying the aqueous solution; The method for producing a negative electrode active material according to claim 9 or 10, comprising:

12. The method for producing a negative electrode active material according to any one of claims 9 to 11, wherein a mixing ratio (molar ratio) of the organic acid magnesium to the sugar is 1:3 to 3:1.

Citation Information

Patent Citations

  • Negative electrode active material for sodium ion secondary battery, production method of the same, and sodium ion secondary battery

    JP2017107856A

  • Negative-electrode active material for sodium-ion secondary battery, method for manufacturing said negative-electrode active material, and sodium-ion secondary battery

    WO2014188722A1

  • Negative-electrode active material for sodium-ion secondary battery, method for manufacturing said negative-electrode active material, and sodium-ion secondary battery

    WO2014188723A1

  • Carbonaceous material for sodium ion secondary battery negative electrode, and sodium ion secondary battery using carbonaceous material for sodium ion secondary battery negative electrode

    WO2017057146A1